Contagious Yawning and Seasonal Climate Variation - Gallup, Andrew C.; Eldakar, Omar T. (Frontiers in Evolutionary Neuroscience, 2011)
Recent evidence suggests that yawning is a thermoregulatory behavior. To explore this possibility further, the frequency of contagious yawning in humans was measured while outdoors in a desert climate in the United States during two distinct temperature ranges and seasons (winter: 22oC; early summer: 37oC). As predicted, the proportion of pedestrians who yawned in response to seeing pictures of people yawning differed significantly between the two conditions (winter: 45%; summer: 24%). Across conditions yawning occurred at lower ambient temperatures, and the tendency to yawn during each season was associated with the length of time spent outside prior to being tested. Participants were more likely to yawn in the milder climate after spending long periods of time outside, while prolonged exposure to ambient temperatures at or above body temperature was associated with reduced yawning. This is the first report to show that the incidence of yawning in humans is associated with seasonal climate variation, further demonstrating that yawn-induced contagion effects can be mediated by factors unrelated to individual social characteristics or cognitive development.